On Gravitational Casimir Effect and Stefan-Boltzmann Law at Finite Temperature - S. C. Ulhoa; A. F. Santos; T. F. Furtado; F. C. Khanna (Advances in High Energy Physics)
Gravitons are described by the propagator in teleparallel gravity in nearly flat space-time. Finite temperature is introduced by using Thermofield Dynamics formalism. The gravitational Casimir effect and Stefan-Boltzmann law are calculated as a function of temperature. Then an equation of state for gravitons is determined.